Cell compensatory responses of fungi to damage of the cell wall induced by Calcofluor White and Congo Red with emphasis on Sporothrix schenckii and Sporothrix globosa. A review - Ortiz-Ramírez, Jorge A.; Cuéllar-Cruz, Mayra; López-Romero, Everardo (Frontiers in Cellular and Infection Microbiology, 2022)
The cell wall (CW) is the outermost layer of fungi and other organisms. It exhibits a dynamic structure and a characteristic chemical composition consisting almost entirely of interacting fibrillar and cementing, amorphous polysaccharides. These are synthesized by a plethora of sugar polymerases and depolymerases encoded by a significant proportion of the fungal genome (around 20% in the case of Saccharomyces cerevisiae). These enzymes act in an exquisitely coordinated process to assemble the tridimensional and the functional structure of the wall. Apart from playing a critical role in morphogenesis, cell protection, viability and pathogenesis, the CW represents a potential target for antifungals as most of its constituents do not exist in humans. Chitin, β-glucans and cellulose are the most frequent crystalline polymers found in fungal CW. The hexosamine biosynthesis pathway is critical for CW elaboration. Also known as the Leloir pathway, this route ends with the formation of UDP-N-GlcNAc after four enzymatic steps that start with fructose-6-phosphate and L-glutamine in a short deviation of glycolysis. This activated aminosugar is used for the synthesis of a large variety of biomacromolecules in a vast number of organisms including bacteria, fungi, insects, crustaceans and mammalian cells. The first, rate-limiting step of the pathway is catalyzed by glucosamine-6-phosphate synthase (L-glutamine:D-fructose-6-phosphate amidotransferase; EC 2.6.1.16; GlcN-6-P synthase), an essential enzyme that has been considered as a potential target for antifungals. The enzyme also plays a key role in other aspects of metabolism, health and aging and it is feedback regulated in eukaryotes by UDP-N-GlcNAc and other factors. The native and recombinant forms of GlcN-6-P synthase has been purified and characterized from both prokaryotic and eucaryotic organisms and it has been demonstrated its critical role in CW remodeling and morphogenesis after exposure of some fungi to agents that stress the cell surface by interacting with wall polymers. This review deals with some of the cellular compensatory responses to Congo Red and Calcofluor White aimed to remodel the wall structure and functionality.